DETERMINANTS OF ACCEPTANCE OF GOING CONCERN AUDIT OPINION ON MANUFACTURING COMPANIES IN INDONESIA - Kenny Ardillah; Anindya Larassati (Accounting Profession Journal (APAJI), 2023)
Many go public companies compete to maintain their business and gain stakeholders’ trust. The company has a responsibility to provide financial statements following Financial Accounting Standard. This research aims to test the influence of the Public Accounting Firm’s reputation, the client’s firm size, and the opinion shopping on the acceptance of going concern audit opinion. The data collection used in this study is from secondary sources from the annual and financial reports. Based on purposive sampling considering specific criteria, 42 samples and 210 data were obtained in this study. The results showed that Accounting Public Firm’s reputation and opinion shopping did not affect the acceptance of going concern audit opinion. The client’s firm size affects the acceptance of going concern audit opinion on manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019.